Balancing livestock production and natural resource use - Louhaichi, Mounir (Food and Agriculture Organization of the United Nations, 2024)
To meet the growing global demand for food, livestock systems must enhance productivity while using natural resources sustainably and minimizing environmental harm. This paper, presented during the FAO Global Conference on Sustainable Livestock Transformation, analyzes the pivotal role of the livestock sector in supporting human diets, providing essential ecosystem services, and sustaining livelihoods. However, livestock production also significantly contributes to environmental challenges such as climate change, water and land overuse, biodiversity loss, and soil degradation. The presentation underscores the importance of regenerative grazing, sustainable land management, improved manure handling, and efficient water and nitrogen use in mitigating these impacts. A shift toward more sustainable livestock systems is crucial to ensuring long-term food security and environmental resilience.